The Anthropology of Love by Ingeborg Bachmann (“War Diary” and “The Book of Franza”) - Yulia Isapchuk (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ., 2024)
The article is dedicated to the study of the work of the Austrian writer Ingeborg Bachmann (1926–1973), which involves the investigation of specific examples of fictional and non-fictional literature using the principles of literary anthropology. In particular, the «War Diary» («Kriegstagebuch», 1944–1945) and the unfinished novel «The Book of Franza» («Das Buch Franza», 1965–1966) are considered comparatively. The purpose of the article is an anthropological analysis of the cultural universality of love, which is based on the author’s own life experience and is artistically reinterpreted in her texts.